Coercivity enhancement by grain refinement for anisotropic Nd2Fe14B-type magnetic powders. (1st January 2016) - Zhang, Yinfeng; Han, Jingzhi; Liu, Shunquan; Wan, Fangming; Tian, Haidong; Zhang, Xiaodong; Wang, Changsheng; Yang, Jinbo; Yang, Yingchang
Graphical abstract: Abstract: Anisotropic Nd–Fe–B magnetic powders with high coercivity of 1440 kA/m as well as maximum energy products of 296 kJ/m 3 were prepared. It was clearly observed that hydrogenation disproportionation desorption recombination (HDDR) process was confined in single crystal particles of Nd–Fe–B alloys. The recombined grains can be refined from 400 to 250 nm. The grain size refinement leads to a coercivity enhancement from 920 to 1440 kA/m. The coercivity enhancement is related to the grain refinement and the resultant formation of uniform Nd-rich grain boundary as strong pinning sites.